Assessing The Impact of Feedback in Basic Life Support (BLS) Training - Turbanova Umida Valiyevna (Global Scientific Publishing, 2023)
This article delves into the core of Basic Life Support (BLS) training, exploring the multifaceted role of feedback in shaping competent and confident responders. BLS, a vital skill set transcending professional boundaries, stands as a lifeline between life and death in emergencies, emphasizing the interconnectedness of actions within the chain of survival. The introduction underscores the transformative power of BLS training, transforming ordinary individuals into potential heroes ready to intervene in critical situations
Keywords: BLS; BLStraining; CPR